2013
DOI: 10.1177/1469787413514648
|View full text |Cite
|
Sign up to set email alerts
|

Student response systems and learner engagement in large classes

Abstract: The use of student response systems is becoming more prevalent in higher level education. Evidence on the effectiveness of this technology can be an important resource for tutors seeking to engage with learners and raise the quality of learning experiences. Student response systems have been found to increase student engagement and participation in the classroom, yet few studies examine why this is so. This research seeks to explore the effects of student response systems on student participation in large clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
152
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(161 citation statements)
references
References 29 publications
5
152
0
4
Order By: Relevance
“…Methods that permit immediate feedback to students during lectures and tests have been shown to increase more effective long-term understanding (Roediger & Butler, 2011). Classroom response systems, for example, have gained considerable acceptance in engaging students during lectures in large classes (Schell, Lukoff, & Mazur, 2013;Heaslip, Donovan, & Cullen, 2014). In addition, continual "retrieval practice" enhanced with rapid feedback has been shown to assist persistent learning (Roediger & Butler, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Methods that permit immediate feedback to students during lectures and tests have been shown to increase more effective long-term understanding (Roediger & Butler, 2011). Classroom response systems, for example, have gained considerable acceptance in engaging students during lectures in large classes (Schell, Lukoff, & Mazur, 2013;Heaslip, Donovan, & Cullen, 2014). In addition, continual "retrieval practice" enhanced with rapid feedback has been shown to assist persistent learning (Roediger & Butler, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A fair number of research studies (e.g., R. Guthrie & Carlin, 2004;Heaslip et al, 2014) on clickers have suggested that students appreciate anonymity for better participation in the class. However, R. Guthrie and Carlin (2004) also revealed that a reasonable percentage of students were not worried about being judged poorly by their peers while answering incorrectly in the classroom.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Of interest for future research is the question of how many paratelic activities should be introduced in the course of a lecture (as per the time specified) so as to maximally optimize student engagement (Heaslip, Donovan, & Cullen, 2014). Several different types of mid-lecture activities can be compared for their relative efficacy in engagement, for example relaxation, taking a minute to review notes or the textbook, or noting a question one might wish to ask (Tangney, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas McKeachie notes the traditional "sage on the stage" method has proven to be largely ineffective, it is undermined by the nature of longer class times (those exceeding 75 minutes), which necessarily require a brief recess to reinvigorate fatigued students; this may come in the form of active learning exercises spaced 10-15 minutes apart (see Heaslip, Donovan, & Cullen, 2014;Tangney, 2014). However, an alternative approach (as hypothesized using Reversal Theory) may help to explain how this same outcome can be achieved in situ, throughout an ongoing lecture.…”
mentioning
confidence: 99%